Designing a Novel Electrolyte Na3.2Hf2Si2.2P0.8O11.85F0.3 for All‐Solid‐State Na‐O2 Batteries. Issue 7 (1st May 2022) - Sun, Qi; Dai, Lei; Tang, Yongfu; sun, Jun; Meng, Weidong; Luo, Tingting; Wang, Ling; Liu, Shan
Abstract: Sodium‐air battery has great development potential due to its high energy density and high safety. However, most previous works are based on liquid electrolyte or polymer electrolyte, which will inevitably result in safety hazards such as electrolyte leakage and sodium dendrite growth. Herein, an all‐solid‐state Na‐O2 battery based on a well‐designed NASICON‐type electrolyte Na3.2 Hf2 Si2.2 P0.8 O11.85 F0.3, which has high ionic conductivity (2.39 × 10 −3 S cm −1 ) and excellent chemical stability, is developed. Collaborating with the reasonable humidity of the atmosphere, the battery shows good cycle stability. This research demonstrates that NASICON‐type electrolyte Na3.2 Hf2 Si2.2 P0.8 O11.85 F0.3 has good application potential for all‐solid‐state Na‐O2 batteries and lays a solid foundation on the material preparation and optimization for developing high‐energy sodium‐air batteries. Abstract : An all‐solid‐state Na‐O2 battery based on a well‐designed NASICON‐type electrolyte Na3.2 Hf2 Si2.2 P0.8 O11.85 F0.3, which has high ionic conductivity (2.39 × 10 −3 S cm −1 ) and excellent chemical stability, is developed. Collaborating with the reasonable humidity of the atmosphere, the battery shows good cycle stability. The research demonstrates that NASICON‐type electrolyte Na3.2 Hf2 Si2.2 P0.8 O11.85 F0.3 has good application potential for all‐solid‐state Na‐O2 batteries.